Portofolio investasi berbasis saham akselerasi - Nathania Rachel Queen Rondonuwu; Monica Kurnia Antou (Yayasan Widyantara Nawasena Raharja, 2023)
The issue of changes in inflation and interest rates from January to April 2023 is likely to have an impact on trading activity in the capital market. The purpose of this study is to analyze the risk-return performance, especially on accelerated trading boards related to changes in inflation and interest rates. This study finds that stock returns on accelerated trading boards throughout the observation period have not achieved optimal performance with low systematic risk. Individually, this study finds that IPAC and RUNS have optimal returns along with inflation and interest rate issues.